Demonstration of a low cost, high temperature elemental sulfur thermal battery. (5th June 2018) - Barde, Amey; Jin, Kaiyuan; Shinn, Mitchell; Nithyanandam, Karthik; Wirz, Richard E.
Highlights: A low-cost, high-temperature (200–600 °C) TES system is demonstrated. SulfurTES temperatures are attractive for many TES applications. Safe and reliable operation of SulfurTES battery for over 10 thermal cycles. SulfurTES battery operated in hybrid thermal charging mode. High volumetric energy density. Abstract: Elemental sulfur is a low-cost energy storage media suitable for many medium to high temperature applications, including trough and tower concentrated solar power (CSP) and combined heat and power (CHP) systems. In this study, we have demonstrated the viability of an elemental sulfur thermal energy storage (SulfurTES) system using a laboratory-scale thermal battery. The SulfurTES battery design uses a shell-and-tube thermal battery configuration, wherein stationary elemental sulfur is isochorically stored in multiple stainless steel tubes and a heat transfer fluid (air) is passed over them through the surrounding shell. The safe and reliable operation was demonstrated for twelve thermal charge–discharge cycles in the temperature range of 200–600 °C, during which the SulfurTES battery stored up to 7.6 kW h of thermal energy with volumetric energy density range up to 255 kW h/m 3 . Furthermore, the SulfurTES battery is operated in a hybrid thermal charging mode to demonstrate its ability to store surplus electrical energy. The present study establishes the feasibility of SulfurTES as a concept that could provide attractive system cost and volumetric energy density for a wide range of thermal energy storage applications.